FACTORS THAT AFFECT THE MANAGER'S PERCEPTION ABOUT THE FACTORS THAT INFLUENCE COMPANY PERFORMANCE (Empirical Study on State-owned enterprises of Indonesia Companies in the Construction Sector in Medan City) - Muliadi, Muliadi (International Journal of Public Budgeting, Accounting and Finance, 2018)
This research aims to know and analyze about Factors That Influence Manager Perception Of Factors Affecting Company Performance (Empirical Study On State Enterprise Of Construction Sector In Medan). This type of research is causal research. The population in this study is State-Owned Enterprise Sector Construction In Medan. The sampling technique used was Purposive sampling with 102 respondents. This research was conducted by the method of spreading the questionnaire to each State-Owned Enterprise of Construction Sector in Medan. Testing of research data using multiple linear regression analysis. The results of this study indicate that the overall variables studied are: Perceptions of Environmental Uncertainty, Managerial Competence, Extent of Coverage Area, Information Technology and Openness of Society in Receiving Development significantly and positively influence on the Performance of State-Owned Enterprise Construction Sector contained in Medan.